Brokers and boundaries : colonial exploration in Indigenous territory - Shellam, Tiffany, 1979-; Nugent, Maria; Konishi, Shino; Cadzow, Allison (Aboriginal history monograph series., 2016)
Colonial exploration continues, all too often, to be rendered as heroic narratives of solitary, intrepid explorers and adventurers. This edited collection contributes to scholarship that is challenging that persistent mythology. With a focus on Indigenous brokers, such as guides, assistants and mediators, it highlights the ways in which nineteenth-century exploration in Australia and New Guinea was a collective and socially complex enterprise. Many of the authors provide biographically rich studies that carefully examine and speculate about Indigenous brokers' motivations, commitments and desires. All of the chapters in the collection are attentive to the specific local circumstances as well as broader colonial contexts in which exploration and encounters occurred.